Analysis The Effect of Solar Radiation on The Efficiency of PV Plant 50 kWp Rooftop UNPAM Viktor - Ojak Abdul Rozak; Rohmat Tri Mulyadi; Hafidz Nurfadilah (UIR PRESS, 2023)
The potential for solar energy in indonesia which is a tropical country is very large with an insolation of around 4.5 Kwh/m2/day. Solar energy in the form of radiation waves will affect the power generated by solar panels and the efficiency of solar panels in generating power. This study was conducted at PV plant pamulang university which has a total of 108 panels with 6 strings and 18 panels in each string. The data in this study were taken per string to see the difference of efficiency in each string. The main problem of this study is to find out how much power and efficiency generated by PV plant against solar radiation. The purpose of this study is to understand and analyze the effect of solar radiation on power and efficiency. The method used is a quantitative descriptive method using a seaward irradiance meter to measure the average daily radiation per string and isolarcloud software to retrieve data from the voltage and current per string. The data taken is then calculated using a formula and then described using tables. Study shows that heat from the weather will result in decreased efficiency and the results of the analysis for a day the average value of radiation is 544.19 w/m2, the average power is 4227.79 watt and the resulting average efficiency is 18.57%.